Crossing African Borders: migration and mobility - Rodrigues, Cristina Udelsmann (2013)
This publication is one of the results of a conference organised in Lisbon in 2011 on the theme of African borders and their relationships with migration and mobility. The selected papers are a sample of the diverse perspectives on the general theme presented at the meeting. The African Borderlands Research Network (ABORNE) promoted this event, allowing a substantial number of its members to exchange results of ongoing and long-term research. The Fundação para a Ciência e a Tecnologia (Portugal) funded the research project Borders and Identity in Africa which prepared this publication.